THE INFLUENCE OF THE WORK ENVIRONMENT AND COMPETENCE ON EMPLOYEE PERFORMANCE AT THE INDONESIAN EMPLOYERS’ ASSOCIATION (APINDO) - Amaliyana Chairunnisa; Adriza; Dudun Junaedi (STMIK Indonesia Banda Aceh, 2026)
This study examines the extent to which the work environment and competence influence employee performance at the Indonesian Employers’ Association (APINDO). A favorable work environment and competence are expected to be factors that can continuously improve employee performance. The objectives are to describe and analyze the work environment, competence, and employee performance, and to estimate the magnitude of the influence of the work environment and competence on employee performance at APINDO, both simultaneously and partially. The research employed a descriptive quantitative approach. The sample consisted of 30 employees of APINDO. Primary data were obtained from respondents’ answers to a questionnaire distributed by the researcher. The results of data analysis indicate that the work environment and competence influence employee performance at APINDO, both partially and simultaneously. Employee performance is explained by the work environment and competence variables by 82.3%, while the remaining 17.7% is attributable to other factors not examined in this study.